(3GdQSGdI GdKGdKI aj GdHGHjIs - (3eLghds
(3ChdgG (B:s
...(3hgPG ef NeQ(B...(3GNJUc Gddg HgG aGTQH aj HjJc SQG dFdG jWdY HgG CMO ef gDdGA GdZGadjf(B...s
(3BNQgG (B:s
...(3Cf GSJbjehG jG bhe Ydi GdUQGW hchfhG Ydi GdCeQ (B...s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds